2004
DOI: 10.1076/chin.9.4.255.23519
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Inhibition, Executive Functioning, and ADHD Symptoms: A Longitudinal Study from Age 5 to 8½ Years

Abstract: The present study examined whether inhibition measured as early as preschool can predict more general executive functioning and ADHD symptoms at school age. In contrast to previous studies, the present study focused specifically on ADHD symptoms rather than general disruptive behavior problems, and boys and girls were studied separately. The main result was that inhibition was strongly related to ADHD symptoms both in school and at home for boys, but only in the school context for girls. Early inhibition was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
97
2
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 20 publications
13
97
2
6
Order By: Relevance
“…Consistent with the literature (Berlin et al, 2003;Campbell et al, 1994;Marakovitz & Campbell, 1998), two of the behavioral inhibition measures (CPT commission errors and DGT) were found to predict ADHD symptoms at first and third grades, and inattention was found to predict ADHD symptoms at first grade. However, as far as we know, the current study is the first to examine and find these effects even after controlling for the longitudinal stability in ADHD symptoms.…”
Section: Summary Of Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Consistent with the literature (Berlin et al, 2003;Campbell et al, 1994;Marakovitz & Campbell, 1998), two of the behavioral inhibition measures (CPT commission errors and DGT) were found to predict ADHD symptoms at first and third grades, and inattention was found to predict ADHD symptoms at first grade. However, as far as we know, the current study is the first to examine and find these effects even after controlling for the longitudinal stability in ADHD symptoms.…”
Section: Summary Of Resultssupporting
confidence: 85%
“…Preschool inhibition deficits predicted later ADHD symptoms both at school and home for boys and in the school context only for girls. Furthermore, Berlin et al (2003) found that preschool inhibition and concurrent executive function measures contributed independently to the variance in ADHD symptoms in school for boys and the sample as a whole. Unlike in the current study, Berlin and colleagues did not examine the predictive association between preschool inattention and ADHD symptoms.…”
Section: Studies Of Inhibition and Adhd Symptoms In Childrenmentioning
confidence: 95%
See 3 more Smart Citations